2005
DOI: 10.1002/eji.200526321
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐activated protein kinase and activator protein‐1 dependent signals are essential for Bacteroides fragilis enterotoxin‐induced enteritis

Abstract: The approximately 20-kDa heat-labile toxin produced by enterotoxigenic Bacteroides fragilis is known to be associated with the development of enteritis. However, the molecular mechanism involved is not yet fully understood. In this study, we assessed whether B. fragilis enterotoxin (BFT)-induced enteritis is related to mitogen-activated protein kinase (MAPK) signaling pathways. In human colon epithelial cells, BFT activated three major MAPK cascades. The activation of p38 was sustained for a relatively long pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 54 publications
5
106
1
Order By: Relevance
“…In addition, transfection experiments using an adenovirus vector containing dominant-negative p38 mutants demonstrated that the suppression of p38 MAPK not only increased DNA fragmentation but also decreased PGE 2 production. These results are consistent with our previous report showing that a p38 inhibitor, SB203580, prevented BFT-induced colitis in the mouse ileum, as evidenced by significant decreases in villous destruction, neutrophil infiltration, and mucosal congestion [8]. These results suggest that MAPK is involved in cell protection in BFT-stimulated epithelial cells, and p38 seems to play a major role in the transcriptional regulation of c-IAP2.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In addition, transfection experiments using an adenovirus vector containing dominant-negative p38 mutants demonstrated that the suppression of p38 MAPK not only increased DNA fragmentation but also decreased PGE 2 production. These results are consistent with our previous report showing that a p38 inhibitor, SB203580, prevented BFT-induced colitis in the mouse ileum, as evidenced by significant decreases in villous destruction, neutrophil infiltration, and mucosal congestion [8]. These results suggest that MAPK is involved in cell protection in BFT-stimulated epithelial cells, and p38 seems to play a major role in the transcriptional regulation of c-IAP2.…”
Section: Discussionsupporting
confidence: 93%
“…To support this hypothesis, the role of IL-8 was at first explored by Sanfilippo et al [10]. In addition, we have reported BFT-induced proinflammatory signals in IEC [6][7][8][9]. In the studies reported here, we found that one of the late responses to BFT stimulation in human IEC is apoptosis in a dose-and timedependent manner.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations